Study Of Hr Management For A Development In Learning Strategies In The New Normal Era - Zulkarnain, Ahnis; Restiana, Rizni (Green Publisher Indonesia, 2021)
This research was conducted by using this literature study to determine: Analysis of HR Management in Improving Learning Strategies in the New Normal Era. In this study, the method used is qualitative with a library research approach. The results of the study show that: HR management in improving learning strategies in the new normal era is through efforts, mature readiness, debriefing both in terms of IT skills and the habit of virtual learning. The most appropriate learning strategy in this new normal era is to follow the rules of the Ministry of Education and Culture with virtual learning through an agreed platform. For this reason, it is necessary to carry out 2 main elements of teaching and learning activities, students and teachers must be equipped, qualified and know the direction of filtered learning in order to minimize misunderstandings between teachers and students. Meanwhile, students at home study with the help and supervision of their parents to avoid cheating, laziness and cheating during exams. So that ethics, values / norms are still upheld in the realm of academia.